Estimating Dynamic Model Parameters for Adaptive Protection and Control in Power System - Ariff,MAM; Pal,BC; Singh,AK (IEEE Transactions on Power Systems, 2014)
This paper presents a new approach in estimating important parameters of power system transient stability model such as inertia constant H and direct axis transient reactance x′d in real time. It uses a variation of unscented Kalman filter (UKF) on the phasor measurement unit (PMU) data. The accurate estimation of these parameters is very important for assessing the stability and tuning the adaptive protection system on power swing relays. The effectiveness of the method is demonstrated in asimulated data from 16-machine 68-bus system model. The paper also presents the performance comparison between the UKF and EKF method in estimating the parameters. The robustness of method is further validated in the presence of noise that is likely to be in the PMU data in reality.